An updated constraint on the local stratigraphy at the Chang'E-4 landing site - YiRen Chang; ZhiYong Xiao; YiChen Wang; ChunYu Ding; Jun Cui; YuZhen Cai (Earth and Planetary Physics, 2021)
The Chang’E-4 mission has been exploring the lunar farside. Two scientific targets of the rover onboard are (1) resolving the possible mineralogy related to the South Pole-Aitken basin and (2) understanding the subsurface processes at the lunar farside. Publications to date that are based on the reflectance spectra and radar data obtained by the rover have shown a persistent inconsistency about the local stratigraphy. To explain both the abnormal surface topography at the landing site and the unexpected radargram observed by the rover, the Alder crater has been frequently reported to be older than the mare basalts at that landing site. However, this argument is not supported by earlier geological mapping nor recent crater statistics. Resolving this controversy is critical for a full understanding of the geological history of the landing area and for correct interpretations of the scientific data returned. Employing detailed crater statistics, rigorous statistical analyses, and an updated crater chronology function, this study is determined to resolve the relative ages of the Alder crater, Finsen crater, and the mare basalts on the floor of Von Kármán. Our results reveal that while background secondaries and local resurfacing have widely occurred in the study area, affecting age determinations, the statistics are significant enough to conclude that the Alder crater is the oldest among the three targets. This independent constraint is consistent with both the crosscutting relationships of different terrains in this area and global stratigraphic mapping. Our results exclude Alder as a possible contributor of the post-mare deposits at the landing site, appealing for a more systematic stratigraphy study to resolve the provenances of these deposits.